2020
DOI: 10.1101/2020.05.28.118703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amnion signals are essential for mesoderm formation in primates

Abstract: The signaling network governing the formation of the primitive streak is well understood in mice, but largely unexplored in primates. Advances in single-cell technology and in vitro embryo culture have enabled to characterize the major cell populations involved. However, a detailed map of this process and insights into its regulatory networks are lacking. Herein, we generated a serial single cell atlas of over 30,000 cells spanning peri-implantation to early primitive streak stages in non-human primates (NHP) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 69 publications
4
38
0
Order By: Relevance
“…Through scRNA-seq of micro-dissected amnion, we found a series of genes differentially expressed between epiblast and amnion ectoderm, including Krt8 , Lrp2 and Wnt6 . Wnt6 is a conserved amnion ectoderm marker in mouse 58 , non-human primate 59 , and human 60 embryos. WNT6 and LRP2 were co-expressed in a subset of human embryo ectoderm cells 60 , similar to what we observed in amnion epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Through scRNA-seq of micro-dissected amnion, we found a series of genes differentially expressed between epiblast and amnion ectoderm, including Krt8 , Lrp2 and Wnt6 . Wnt6 is a conserved amnion ectoderm marker in mouse 58 , non-human primate 59 , and human 60 embryos. WNT6 and LRP2 were co-expressed in a subset of human embryo ectoderm cells 60 , similar to what we observed in amnion epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was thought that detectable phenotypes for loss-of-function mutations of pathway components do not emerge before implantation (Beppu et al, 2000;Chu et al, 2004;Sirard et al, 1998;Yang et al, 1998), recent studies suggest that loss of BMP signaling leads to impaired development of the TE and PrE lineages (Graham et al, 2014), and that its role in the TE lineage is to maintain the stem cell population (Sozen et al, 2021). ), BMP4 is suggested to be expressed in amnion and induces primitive streak formation in the adjacent epiblast (Yang et al, 2020).…”
Section: Bmp Wnt Fgf and Nodal Signaling In Early Embryosmentioning
confidence: 99%
“…During human embryogenesis, the amnion differentiates from the EPI before gastrulation. Recently, it has been suggested that amniotic cells may serve as sources for gastrulation-inducing signals in primate embryos (Sasaki et al, 2016;Yang et al, 2020) (Figure 1B); however, until recently, systems to study human amniotic development were lacking. hESCs grown on a gel bed with gel supplemented into the media will differentiate into 3D sacs consisting of amniotic tissue in a manner requiring BMP activity (Shao et al, 2017a).…”
Section: Human Post-implantation Amniotic Sac Embryoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amnion express components of WNT (WNT3, WNT6, and AXIN), BMP4/TGF-β (BMP4, ID2, and MSX2) and PI3K/Akt signaling pathways ( Sasaki et al, 2016 ; Niu et al, 2019 ; Yang et al, 2020 ) during the cyno embryo development. The BMP4 decreased by the loss of ISL1 in the amnion induces a failure in the mesoderm formation of the posterior epiblast in this species ( Yang et al, 2020 ). The amnion may also have an essential role in the PGC specification via BMP4 and WNT3 ( Sasaki et al, 2016 ).…”
Section: Possible Role Of the Amnion In The Anterior-posterior Regionalizationmentioning
confidence: 99%